2016
DOI: 10.1136/bmjopen-2016-012870
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of social and economic factors to mental disorders among population-based samples of Jamaicans and Guyanese

Abstract: BackgroundThere have been growing concerns about increasing mental health problems in the Caribbean region. This study explores rates and factors associated with selected mental health disorders within 2 Caribbean countries: Jamaica and Guyana.MethodsProbability samples of 1218 Jamaicans and 2068 Guyanese participants were used. A modified version of the WHO Composite International Diagnostic Interview (WHO CIDI) defined by the Diagnostic Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
9
1
Order By: Relevance
“…Abstinence from alcohol consumption was found to be a protective factor against mental health problems. This finding is consistent with the results of Lacey et al [ 43 ]. Petroleum workers spend prolonged periods of time in a unique environment, and are often subjected to noise and heavy workloads.…”
Section: Discussionsupporting
confidence: 94%
“…Abstinence from alcohol consumption was found to be a protective factor against mental health problems. This finding is consistent with the results of Lacey et al [ 43 ]. Petroleum workers spend prolonged periods of time in a unique environment, and are often subjected to noise and heavy workloads.…”
Section: Discussionsupporting
confidence: 94%
“…First, epidemiological studies suggest a greater ratio of men suffering from schizophrenia (Aleman et al, 2003;Leung and Chue, 2000;Ochoa et al, 2012). This male predominance seems to be associated across different regions with a higher comorbidity of substance abuse in men (Aleman et al, 2003;Lacey et al, 2016;Leung and Chue, 2000;Ochoa et al, 2012). Likewise, in this study comorbid SUD was present in 52.1% of the male patients compared to 7.3% of the female patients.…”
Section: Discussionsupporting
confidence: 46%
“…Likewise, in this study comorbid SUD was present in 52.1% of the male patients compared to 7.3% of the female patients. Second, SUD in male patients may trigger violent behavior and precipitate psychotic disorders and is associated with poverty and social isolation (Aleman et al, 2003;Lacey et al, 2016;Marconi et al, 2016;Ochoa et al, 2012;Roncero et al, 2014). Hence, male patients with SUD are more likely to commit socially disruptive behaviors leading to (forced) hospitalizations (Farabee and Shen, 2004;Mitchell et al, 2009;Vancampfort et al, 2016a, b;Virmani et al, 2006Virmani et al, , 2007.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A regional study reporting data from nine Caribbean countries on adolescents age 10–18 indicated that 1 in 6 (17%) adolescents saw themselves as sad, angry or irritated [ 23 ]. Country specific data also highlighted a 7.4% rate of depression among CYP in Jamaica [ 24 ], and 14% in Trinidad and Tobago [ 25 ]. Another study conducted in Jamaica, The Bahamas, St Kitts and Nevis and St Vincent and the Grenadines revealed that among the sample of n = 1955 adolescents nearly half of the sample (52.1%) reported mild to severe symptoms of depression and a further 29.1% reported moderate to severe symptoms [ 26 ].…”
Section: Introductionmentioning
confidence: 99%